2018
DOI: 10.1016/j.rboe.2017.03.013
|View full text |Cite
|
Sign up to set email alerts
|

CT-guided percutaneous sacroiliac stabilization in unstable pelvic fractures: a safe and accurate technique

Abstract: ObjectiveThe use of open reduction and internal fixation (ORIF) for unstable pelvic injuries is associated with extensive blood loss, iatrogenic neurovascular injury, and infection. Moreover, the placement of sacroiliac (SI) screws is a blinded procedure, guided primarily by palpation and two-dimensional radiological screening, which demands expertise. The complex three-dimensional anatomy of SI joint and its proximity to neurovascular structure require a safe and precise technique. Computed tomography (CT)-gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…Two articles were prospective [12,13]. 10 articles were retrospective [14][15][16][17][18][19][20][21][22][23].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Two articles were prospective [12,13]. 10 articles were retrospective [14][15][16][17][18][19][20][21][22][23].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…ROBIN: ; DECT: Dual-energy CT; ED: Emergency department; FFP: Fresh frozen plasma; MDCT: Multidetector CT; PXR: Pelvis x-ray; SI: Sacro-iliac A single-stage CT scan considerably reduced the time to definitive pelvic fixation, was utilized to assess the presence or absence of internal organ injury or hemorrhage, and was integrated with 3D pictures to aid surgical planning [18][19][20]. In the emergency room, a pelvic X-ray may help diagnose severe pubic symphysis diastasis.…”
Section: Table 2: Clinical Characteristics and Outcomes Of The Includ...mentioning
confidence: 99%
“…CT-guided iliosacral fixation offers direct visualization of the screws, thus reducing the malposition of the screws and radiation dose. This procedure provides a precise geometry of fracture fragments and anatomical structures, allowing an accurate insertion [ 11 , 12 , 13 , 14 ].…”
Section: Recent Workmentioning
confidence: 99%
“…With the development of digital orthopedics, a variety of auxiliary screw placement technologies have emerged to enable precise sacroiliac screw placement. Gandhi et al demonstrated that CT-guided SI joint stabilization offers many advantages, including safe and accurate screw placement, reduced operating time, early definitive fixation, immediate mobilization, and fewer infections and wound complications [ 5 ]. Takeba et al also achieved satisfactory clinical results using O-arm-assisted nail placement technology [ 6 ].…”
Section: Introductionmentioning
confidence: 99%